PELATIHAN PEMBUATAN PESAWAT RC AERMODELING SISWA SMK PENERBANGAN TECHNO TERAPAN MAKASSAR - Khaidir Rahman; Ervi Novitasari; Nur Rahmah; Andi Muhammad Akram Mukhlis; Amirah Mustarin; Purnamawati; Nurul Fadhilah (TEKNOVOKASI : Jurnal Pengabdian Masyarakat, 2023)
The partner in the Community Partnership Program (PKM) is the Makassar Applied Techno Flight Vocational School. The problems found in students of the Aircraft Electronics Instrument Maintenance and Repair study program and the Maintenance and Repair of Aircraft Motors and Aircraft Frames study program are that in general they still have minimal ability in the field of aircraft because learning facilities in the form of trainers or simulators are still very limited, so competence What is owned is still theoretical, apart from that the internship places for students are still very limited in the Makassar area which is linear with their competence. This training aims to improve students' understanding and skills in the technical field of aircraft. The method applied to this training is descriptive method, with a lecture, discussion, and demonstration approach. The expected outcome of this training is that students can improve their competence theoretically and practically in the field of RC Aeromodeling aircraft which have the same working principle as conventional aircraft.